Thicker than water : [large type] a memoir - Washington, Kerry, 1977- (Little Brown Spark, 2023)
In her memoir, the award-winning actor and activist provides an intimate view into both her public and private worlds as she chronicles her life's journey thus far, sharing how she discovered her truest self and, with it, a deeper sense of belonging.